Vertex markers: Modification of grid methods as markers to reproduce large size augmented reality objects to afford hands - Wahyu Teja Kusuma; Ahmad Afif Supianto; Herman Tolle (Institute of Advanced Engineering and Science, 2020)
The weakness of the research on developing Marker Based Augmented Reality applications found is using small digital content. Weakness is caused by the area of view of Augmented Reality cameras is limited by the placement of markers that are affordable to the user's hand. This study reproducing large digital objects by cutting large digital objects into many pieces. But to keep continuity accuracy between digital object pieces, this study aims to modify the grid method to become a vertex marker. Vertex marker is produced by removing the edge and using the vertex to place the marker. Vertex markers inherit the advantages of the Grid method. Therefore, vertex markers can be used to reproduce large digital objects accurately and can be reached by hand when displayed. The aim of this study is to measure the accuracy of the grid method that has been modified into a marker. The fundamental contributions and advantages of the vertex marker are innovations in the field of Marker Based Augmented Reality research.